A comparison of the Nix Colour Sensor Pro™ and HunterLab MiniScan™ colorimetric instruments when assessing aged beef colour stability over 72 h display. (January 2019) - Holman, Benjamin W.B.; Hopkins, David L.
Abstract: We compared the capacity for the Nix Colour Sensor Pro™ (NIX) and HunterLab MiniScan™ (HUNTER) to detect colour variation using aged (0, 3 and 5 weeks) and then displayed (0, 1, 2 and 3 d) beef M. longissimus lumborum samples ( n  = 8). NIX L* and hue values were found to be respectively higher and lower than for the HUNTER. No significant interactions between instrument and display or ageing periods were identified for a* – unlike for b* and chroma where NIX measures were observed to be lower than those from the HUNTER. Both instruments identified ageing and display period effects on colorimetric traits. Based on these results, the NIX cannot be considered comparable to the HUNTER when measuring beef colour – albeit captured similar colorimetric trends over display and ageing periods which suggest its independent usefulness to beef colour assessment.